Research Progress in Short-Chain Fatty Acid Modulation of the Gut-Bone Axis in Bone Metabolism - ZHANG Xuan, YANG Xue, LI Xinke, MENG Lu, WANG Jiaqi, ZHENG Nan (Shipin Kexue)
As global aging intensifies, the incidence of age-related bone metabolic disorders, such as osteoporosis, continues to climb. Seeking safe and effective therapeutic interventions is of utmost importance. The modulation of bone metabolism by the gut microbiota and their metabolites has emerged as a focal area of research. Short-chain fatty acids (SCFAs), including acetic, propionic, and butyric acids, exert regulatory effects on bone formation and resorption through the gut-bone axis. Furthermore, SCFAs play positive roles in maintaining bone homeostasis and contribute to the alleviation of inflammatory bone loss. This review synthesizes the current knowledge about the mechanism by which SCFAs regulate bone metabolic homeostasis via endocrine pathways, immune modulation, and enhanced nutrient absorption, hoping to provide a scientific foundation for the prevention and treatment of metabolic bone diseases in the elderly.